A Novel Idea of Sulfamic Acid as an Efficient Catalyst for the Synthesis of 2-Azapyrrolizidine Derivatives - Tafer, Radia; Boulcina, Raouf; Debache, Abdelmadjid (Current Organocatalysis, 2023)
Background: The synthesis of 2-azapyrrolizidine scaffolds has fascinated scientists due to their potential biological activities. Objective: An efficient and environmentally sustainable synthetic method has been presented to synthesize structurally various 2-azapyrrolizidines via a three-component reaction. Methods: The condensation of aldehydes, hydantoin, and malononitrile in the presence of green and sustainable sulfamic acid as catalyst in mild conditions has been achieved. Results: The present protocol leads, in most cases, to the desired products in high yields. Conclusion: The synthetic efficiency and operational simplicity make the present procedure cost effective, time efficient and eco-friendly for the synthesis of substituted 2-azapyrrolizidines.
Keywords: hydantoin